Blood Pressure Stability In Relation To Dietary Patterns Among Hypertensive Patients At Sukodono Public Health Center - Nur Aini, Intan; Suprianto; Loetfia Dwi Rahariyani; Moch. Bahrudin (Global Ten Public Health and Nursing Journal, 2025)
Hypertension, a highly prevalent non-communicable disease, can lead to serious complications including kidney failure and stroke. It is well recognized that unhealthy dietary patterns significantly influence blood pressure stability. This study aimed to examine the correlation between dietary habits and blood pressure stability among individuals with hypertension at Sukodono Primary Health Center. A cross-sectional methodology with a quantitative descriptive design was employed. The sample, obtained through consecutive sampling, consisted of 43 respondents. Data were collected using a Food Frequency Questionnaire (FFQ) and direct blood pressure measurements taken during three visits. Descriptive analysis with frequency and percentage distributions was applied. The findings showed that 17 respondents (40%) had unhealthy dietary habits, while 26 respondents (60%) reported healthy dietary patterns. Sixteen respondents (37%) experienced unstable blood pressure, whereas 27 respondents (63%) had stable blood pressure. The majority of respondents with healthy dietary patterns generally maintained stable blood pressure (96%), while most of those with unhealthy dietary patterns demonstrated unstable circulation (88%). This study concludes that nutritious food intake is strongly correlated with blood pressure stability in hypertensive patients. At the primary care level, modifying diets to reduce saturated fat and salt while increasing the intake of fruits and vegetables represents an essential strategy for managing hypertension